Liberalism, torture, and global constitutionalism - Lang, Anthony F. (Contesting torture, 2023)
Torture continues to be practised around the world, despite numerous prohibitions against it. How can it be limited if not halted? In this chapter, I argue that global constitutionalism provides one way for limiting the practice of torture. Rather than relying solely on laws or rules, a constitutional order integrates the law with political power and normative ideals. Liberal ideals of liberty, individualism, and materiality provide a deep normative basis for prohibiting torture. A separation of powers and limits on the executive power provide practical reinforcements to laws outlawing torture. If such a liberal constitution is global, it avoids, or at least lessens, the security discourse that often overrides liberal constitutionalism in domestic orders. Reinforcing not only the legal limits, but empowering institutions and agents at the global level will help to limit the practice of torture. The chapter draws on the liberalism of Judith Shklar to provide the foundations for this argument. It looks to examples drawn from various empirical studies to demonstrate how such a project might work.